Comparison of the Efficacy and Safety of a Doravirine-Based, Three-Drug Regimen in Treatment-Naïve HIV-1 Positive Adults: A Bayesian Network Meta-Analysis - Zhang, Ke; Zhang, Yang; Zhou, Jing; Xu, Lulu; Zhou, Chi; Chen, Guanzhi; Huang, Xiaojie (Frontiers in Pharmacology, 2022)
Introduction: Extensive use of antiretroviral therapy has remarkably improved the survival rates of people living with HIV. Doravirine (DOR) is a newly-approved antiretroviral belonging to the class of non-nucleoside reverse transcriptase inhibitors. Here, we compared the efficacy and safety of DOR+tenofovir dipivoxil fumarate (TDF)+Lamivudine (3TC)/Emtritabine (FTC) with traditional triple therapies in treatment-naïve HIV-1-positive adults. Methods: Randomized controlled trials involving treatment-naïve HIV-1-positive adults that met inclusion criteria were systematically retrieved and data on the following outcomes extracted: virological suppression, adverse events, severe adverse events, and drug-related adverse events. A Bayesian network meta-analysis was then performed on the data. Results: This study included a total of 39 randomized controlled trials involving 26 antiretroviral therapies and 21,110 HIV1-positive patients. At week 48, relative to the other 25 regimens included in the network of virological suppression, DOR+TDF+3TC/FTC exhibited superiority to some efavirenz, nevirapine, atazanavir, or lopinavir-based regimens, including efavirenz+abacavir+3TC (Odd Ratio [OR]=0.52, 95% confidence interval [CrI]=0.35-0.77). At week 48, the performance of DOR+TDF+3TC/FTC was relatively similar to all other analyzed regimens in terms of adverse events. The DOR+TDF+3TC/FTC regimen performed better in terms of severe adverse events and drug-related adverse events. Conclusion: The network meta-analysis showed that DOR+TDF+3TC/FTC has good efficacy and safety at 48 weeks.